Psychological, Physiological, and Physical Effects of Resistance Training and Personalized Diet in Celiac Women - Alejandro Martínez-Rodríguez; Alejandro Martínez-Rodríguez; Daniela Alejandra Loaiza-Martínez; Daniela Alejandra Loaiza-Martínez; Javier Sánchez-Sánchez; Jacobo Á. Rubio-Arias; Fernando Alacid; Soledad Prats-Moya; María Martínez-Olcina; Rodrigo Yáñez-Sepúlveda; Nuria Asencio-Mas; Pablo J. Marcos-Pardo; et al. (Frontiers in Nutrition, 2022)
BackgroundGluten intolerance is a systemic process of autoimmune nature; it develops in genetically predisposed subjects with gluten ingestion. The only treatment for celiac disease (CD) is a lifelong strict gluten-free diet (GFD). This study was designed to evaluate adherence to a GFD, risk of an eating disorder, and nutritional status in adult CD patients undergoing different interventions.MethodsA total of 28 Spanish women, aged 40 years or more, took part in a randomized controlled trial. Each group received a different intervention: group 1, gluten-free nutrition plan + exercise (GFD + E); group 2, gluten-free nutrition plan (GFD); group 3, celiac controls (NO-GFD); and group 4, non-celiac controls (CONTROL). The training was prescribed by a sport scientist. It was based on resistance training with elastic bands; beforehand a warm-up was performed and the resistance was increased progressively. The variables studied were adherence to the GFD, risk of eating disorders, blood values, and body composition.ResultsCeliac women with personalized nutritional planning presented greater adherence to a gluten-free diet (p < 0.001). Regarding leukocytes, significant differences were observed between the GFD and control groups (p = 0.004). Perimeters and folds did not decrease significantly.ConclusionWomen with celiac disease who follow an adapted and personalized diet have a better adherence to a GFD compared to those who follow a non-professional diet, and therefore have a better immune system status (blood leukocytes).